Effectiveness of Content Marketing, Influencers, and TikTok Social Media on Purchase Decisions - Nur Febriyantie; Nur Hayati (Universitas KH. Abdul Chalim Mojokerto, 2025)
In this study, we look at how well content marketing and social media platforms like TikTok work to sway consumers' purchasing decisions, utilizing Cho-Cweet products in Bandung City as a case study. A quantitative approach was employed, featuring descriptive and multiple regression analysis to explore the relationships among these variables. Data were collected from 300 respondents who actively engage with Cho-Cweet content on TikTok, using a purposive sampling technique. The findings reveal that an individual's propensity to make a purchase is positively affected by content advertising as well as social media, while the influence of Influencers was not found to be significant. The research concludes that effective content and social media strategies are essential for driving consumer engagement and sales in the digital market.